2019
DOI: 10.1007/s10664-019-09713-w
|View full text |Cite
|
Sign up to set email alerts
|

To react, or not to react: Patterns of reaction to API deprecation

Abstract: Application Programming Interfaces (API) provide reusable functionality to aid developers in the development process. The features provided by these APIs might change over time as the API evolves. To allow API consumers to peacefully transition from older obsolete features to new features, API producers make use of the deprecation mechanism that allows them to indicate to the consumer that a feature should no longer be used. The Java language designers noticed that no one was taking these deprecation warnings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Later, they further conducted semi-structured interviews [44] with 17 third-party Java API producers and survey 170 Java developers to gain a deep understanding of the requirements regarding deprecation from API producers and consumers. More recently, they extracted the patterns of reaction to API deprecation to ascertain the scale of reactions or non-reactions of users to deprecated entities [47]. These work mainly focused on analyzing the impact of API changes [16,17,25,26,28], but they did not investigate how API contributors handle (i.e., declare and document) API deprecations explored in our work.…”
Section: Related Workmentioning
confidence: 99%
“…Later, they further conducted semi-structured interviews [44] with 17 third-party Java API producers and survey 170 Java developers to gain a deep understanding of the requirements regarding deprecation from API producers and consumers. More recently, they extracted the patterns of reaction to API deprecation to ascertain the scale of reactions or non-reactions of users to deprecated entities [47]. These work mainly focused on analyzing the impact of API changes [16,17,25,26,28], but they did not investigate how API contributors handle (i.e., declare and document) API deprecations explored in our work.…”
Section: Related Workmentioning
confidence: 99%
“…As these API changes are inevitable in the software eco-system, the developers have to adapt to the changes immediately. 43 In previous studies, [24][25][26]44 several attempts have been made to understand the developers' reactions to such API changes. The API changes make the developers depreciate their repositories as they could not cope with the rapid changes.…”
Section: Msr About Impact Of Api Changesmentioning
confidence: 99%
“…In the literature, there are several studies [24][25][26] on understanding the impact of API changes. Specifically, studies such as Salza et al, 27,28 Lamothe et al, 29 and Derr et al, 30 reported the API changes in the Android platform.…”
mentioning
confidence: 99%
“…Many other facets of APIs have been studied, for instance, with respect to their evolution, [53][54][55][56] popularity, [57][58][59] impact on client applications, [60][61][62][63] breaking changes, [63][64][65][66] deprecation, [67][68][69][70][71] reasons to change, 65,72 to name a few.…”
Section: Api Examples and Api Researchmentioning
confidence: 99%